DESIGN OF TOURISM SOUVENIR BASED ON INTANGIBLE CULTURAL HERITAGE: CHINESE THEATER ARTS CASES - Yezhova, O.; Gao, H. (Art and Design, 2023)
The purpose: investigate and analyze the current status of intangible cultural heritage tourism products, explore their development and existing issues, and propose directions and principles for design research regarding the inheritance of intangible cultural heritage, on the example of Chinese theatrical art. Methodology. Adopting an integrated approach that combines theory and practice, this study conducts a literature review and analysis of relevant scholarly publications to summarize the current status of intangible cultural heritage tourism souvenirs. It synthesizes the issues associated with these souvenirs and explores the directions for design research of intangible cultural heritage tourism souvenirs. The cases of Shadow puppetry and Sichuan Opera souvenirs are investigated. Results. Propose principles and guidelines for the design of intangible cultural heritage tourism products based on Chinese theatrical art, explore successful design cases of intangible cultural heritage tourism products through case studies and empirical research, and provide practical design ideas and methods for relevant practitioners. The scientific novelty lies in the analysis and summary of previous research, identifying existing problems and beneficial solutions, exploring the design research directions of intangible cultural heritage tourism souvenirs, and providing recommendations for relevant researchers. Practical significance. The results of this study can be applied to the design practice of tourism souvenirs in cultural heritage, including both tangible and intangible cultural heritage.